ANALISIS TINGKAT KEPUASAN PASIEN PENGGUNA BPJS KESEHATAN TERHADAP PELAYANAN DI RSUD KOTA PADANG PANJANG SUMATERA BARAT - Balqis Tsania Salsabilla; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research was conducted at the Padang Panjang Regional General Hospital. The purpose of this study was to find out:1) To find out the level of patient satisfaction using BPJS for Padang Panjang City Hospital services 2) To find out the factors that influence patient satisfaction using BPJS. This research uses descriptive quantitative method. The population of this study were patients using BPJS Health who were treated at Padang Panjang City Hospital, totaling 6,390 people and the sample in this study were 98 respondents. Sampling using accidental sampling technique. Data instruments are Observations, Questionnaires and Interviews. Based on the results of the study it can be concluded that patient satisfaction based on administrative process service indicators is classified as satisfied with a frequency of 69 respondents, satisfaction with services on physical evidence indicators is stated to be satisfied with a frequency of 73 respondents, based on indicators of reliability the officers have provided good service, expressed by respondents giving good assessment with a frequency of 85 people, the responsiveness of the officers was good so that respondents were satisfied with a frequency of 61 people. Good empathy with a frequency of 76 respondents. Good service will have an impact on patient satisfaction, the better the service provided by officers, the higher the level of patient satisfaction. Keywords: Analysis, Satisfaction, Service